Shopping Motivation on Purchase Intention: Can Loyalty Program and Corporate Image Enhance Such Relationship? - Rahmawati Rahmawati; Ben Roy Do (APMBA (Asia Pacific Management and Business Application), 2014)
Previous studies of shopping motivation as well as research to classify the various customers into group or types. This present study intends to take the first steps towards the development of shopping motivation may have effect on purchase intention with moderating role of loyalty program and corporate image in hypermarket format. The sample of 228 undergraduate and post graduate student where they had visited a hypermarket. Hierarchical regression was conduct to analysis that such of relationship. In this study was divided into 4 model including control variable, predictor variable, two way interaction and three way interaction. The result indicated that shopping motivation was statistically significant can increase purchase intention. Loyalty program and corporate image as not moderating variable, because the two interactions is not significant. However, loyalty program can affect independently (as predictor variable) on purchase intention. Shopping motivation and loyalty program may be the good combination of marketing strategy to increase purchase intention in retail format. In the future research, suggested using another variable such that store atmospheric, promotion strategy or other variable as moderating variable and also general public as respondent is the best sample.